Comparison of consistency assessment models for isolated horizontal curves in two-lane rural highways (2015)
This consistency assessment of highways’ geometrical design has the objective of providing safer roads. There are two types of models for consistency assessment: aggregated and disaggregated. The first one considers the difference between design and operating speed at the middle point of isolated horizontal curves. The second one considers the spatial variation of the operating speed profile along the horizontal curve. This paper compares the two types of consistency assessment models, using naturalistic speed and geometry data obtained in 34 horizontal curves of two-lane rural roads in Chile, using a 10 Hz GPS. Results obtained showed that in only 19 cases both methods are equivalent. This equivalence occurred only when operating speed profiles have the lowest spatial variance along the curves. If the operating speed profile has a high variance the consistency level obtained using both methods is different and the better option is combine it.